2020
DOI: 10.7759/cureus.8892
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Presentation of Parsonage-Turner Syndrome

Abstract: Ibrahim et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The diagnosis is primarily clinical, based on a thorough medical history and pathological findings in the physical examination and electromyographic (EMG) exam. Additional diagnostic work-up, including laboratory and imaging, offer support mainly by ruling out other possible etiologies [5] , [6] , [7] . Therefore, PTS should always be considered in the differential diagnosis of acute-onset shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is primarily clinical, based on a thorough medical history and pathological findings in the physical examination and electromyographic (EMG) exam. Additional diagnostic work-up, including laboratory and imaging, offer support mainly by ruling out other possible etiologies [5] , [6] , [7] . Therefore, PTS should always be considered in the differential diagnosis of acute-onset shoulder pain.…”
Section: Discussionmentioning
confidence: 99%
“…[1,6] the literary data available, only a few cases with the clinical presentation of painless neuralgic amyotrophy after surgery or vaccination have been reported. [7,8] Treatment is supportive, as there are currently no evidence based pharmacological or rehabilitation interventions. [8,9,10,11] In our patient, the initial signs were motor weakness and muscle atrophy, which progressed for about 3 weeks after the inciting event; actually, the lack of pain was the atypical manifestation of this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…This is the main study limitation. Ibrahim et al [ 37 ] claimed that although physiotherapy improves and alleviates PTS symptoms, it does not improve recovery duration. Tsairis et al [ 4 ] reported that a recovery in 80% of patients with PTS occurs after two years, and 89% after three years.…”
Section: Discussionmentioning
confidence: 99%